Peningkatan Pengetahuan Masyarakat Desa Bungatan Kabupaten Situbondo Tentang Sanitasi Lingkungan - Bambang Sri Kaloko; Lestyo Wulandari; M. Zainal Roisul Amin; Muhamad Khoirul Anam (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
KKN is activities carried out by students to integrate academic learning with practical experience in the field. Students who undergo KKN will socialize with the surrounding community, identify problems that occur at the KKN location, and find solutions that are relevant to these problems. The results of problem identification by students in Bungatan Village were the lack of public concern for environmental cleanliness and the absence of a Garbage Disposal Site. For this reason, group 160 KKN students stationed in Bungatan Village held a socialization activity on Bungatan Can Clean from Garbage (Busa-Busa). The activity aims to provide knowledge to the Bungatan Village Community regarding the types of waste, how to manage it, and invite all elements of the village apparatus to hold TPS and waste management from TPS to TPA. After this activity, it is hoped that the Bungatan Village Community will become more concerned with the surrounding environment.